Factors that influence the decision to vape among Indigenous youth - Laura L. Struik; Saige-Taylor Werstuik; Alyssa Sundstrom; Sarah Dow-Fleisner; Shelly Ben-David (BMC, 2022)
Abstract Background The use of e-cigarettes (vaping) among Indigenous youth is much higher than that of their non-Indigenous counterparts, which has raised the concerns of various Indigenous scholars and communities. To better understand the most salient constructs that influence Indigenous youth decision-making around vaping, we co-created a qualitative research study with a Syilx First Nation community that was guided by the Unified Theory of Behavior (UTB). Methods Through semi-structured interviews and a sharing circle, we gathered the perspectives and experiences of 16 Syilx youth in British Columbia, Canada. After an initial collaborative coding and training session, the interviews were transcribed and coded by Indigenous peer researchers using Nvivo. Through both directed and conventional qualitative content analysis methods, the final conceptual framework was collaboratively developed. Results Syilx youth reported that vaping decision-making is underpinned by colonialism, and the historical disproportionate impact of the tobacco industry. The youth spoke to several individual determinants that influence intentions to vape (e.g., vaping helps you cope) and to not vape (e.g., family and community connectedness), and determinants that translate intentions to vape to decision to vape (e.g., access to vaping), and to not vape (e.g., access to trusted adults and support from the band). The youth suggested that prevention efforts must be informed by an understanding of why Indigenous youth vape and what strengthens their resolve to not vape. Conclusions Vaping decision-making among Indigenous youth is underpinned by their cultures, contexts, and histories. To effectively address vaping among Indigenous youth, continued engagement of Indigenous youth in planning, developing, implementing, and evaluating both prevention and policies efforts is a necessity.